Students' Perceptions of ChatGPT as a Learning Aid in Arabic Language Education at Universitas Islam KH. Ruhiat Cipasung - Muttaqin, Cecep; Nukman, Nukman; Hidayat, Ahmad Fadhel Syakir; Lestari, Lita; Taufiq, Furqon; Sofian, Ganjar Yusup (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Along with the rapid development of artificial intelligence technology, ChatGPT, as one of the AI-based learning tools, is increasingly used across various educational sectors. However, are students truly prepared to embrace this change in Arabic language learning? This research is essential to investigate how students of Arabic Language Education at Universitas Islam KH. Ruhiat Cipasung responds to the use of ChatGPT, given that this application offers easy access to information but also brings potential negative impacts that have not been widely discussed. This study aims to explore students’ perceptions regarding the benefits, challenges, and impacts of using ChatGPT in Arabic language learning. This research employs a qualitative approach, utilizing in-depth interviews with students as participants. The results show that while students view ChatGPT as a tool that can accelerate information access and enhance learning efficiency, they also identify several limitations, such as a lack of understanding of cultural and religious contexts, technical issues, and concerns about over-reliance on technology, which could diminish critical thinking skills. This study offers recommendations to strike a balance between the use of ChatGPT and traditional teaching methods that emphasize direct interaction and discussion, thereby creating a balance between technology and social skills in Arabic language education.